Prevalence of Malaria among Patients Visiting Public Hospitals in Mogadishu, Somalia-Cross-Sectional Study - Abdi, Mohamed Salad (Multidisciplinary Journal of Horseed International University (MJHIU), 2024)
Background: In tropical and subtropical areas, malaria is one of the main causes of death and morbidity. Malaria is a major worldwide health concern, especially in sub-Saharan Africa, which includes Somalia, where the majority of cases and deaths from the disease occur. Malaria has a negative impact on both public health and the economic growth of many developing nations. Examining and quantifying the prevalence of malaria among outpatients who have visited hospitals were the study's goal. Study was conducted between September, and November 2023. Methods: A structured questionnaire was administered to 278 were collected patients visit two general hospitals at single time with obtained consented, blood samples were diagnosis used by rapid diagnosis test (RDTs), this study was identified the species of plasmodium used standard keys. Thus, this study design was cross-sectional and quantitative study. The data source was primary information, and was nonrandom sampling. The data generated was analysis using percentage and present in graph forms. Chi- square was used to determine the degree of association between malaria prevalence and factors influencing its transmission, performed by (SPSS 20 version). Results: total of 278 was recruited to conduct the study at outpatient department OPD in two hospitals, Mogadishu, Somalia. Out of 278 persons examined for malaria parasites, 12 (4.3%) were positive. Females were more participated than males 185 (66.5%). The respondents were observed 43.5% use it most of the time sleep under mosquito net. Conclusion: The investigation clearly showed that the persons with malaria infection was minimal. Because the participants aware of the threat posed by mosquitoes in their area, they placed a strong emphasis on vector control measures as reduce the number of mosquito breeding sites. They also understood the significance of indoor residual spray (IRS), which is essential for both mosquito prevention and control.